Morphological and bio-agronomic evaluation of populations of Scorpiurus subvillosus L. - Sortino O.; Gresta F.; Avola G.; Abbate V. (Sustainable Mediterranean grasslands and their multi-functions, 2008)
With the aim of improving the quantitative traits of native pastures of the Hyblean plateau, 4 Sicilian populations and 7 selected lines (for flowering earliness and seed production) of Scorpiurus subvillosus L. were evaluated on plant spaced plots. Morphological (plant height, diameter of plant and length of the longest ramification, in three different periods), phenological (flowering time, duration of the flowering period and pod ripening), and productive (seeds per plant, weight of 1000 seed) parameters were measured. Positive correlations emerged among morphological traits and the length of flowering. Namely, early flowering ecotypes showed greater seed production. The PC analysis concludes that selected lines maintained the characteristics for which they had been selected. Moreover, two populations showed high seed production as well, but with a later flowering and pod ripening. Anyway, the observed variability could contribute to enhancing the genetic improvement of the species for other traits.
12. Meeting of the Sub-Network on Mediterranean Forage Resources of the FAO-CIHEAM Inter-regional Cooperative Research and Development Network on Pastures and Fodder Crop, 2008/04/09-12, Elvas (Portugal)